IMPLEMENTASI ALGORITMA REGRESI LINEAR BERGANDA UNTUK MEMPREDIKSI PRODUKSI PADI DI KABUPATEN BANTUL - Ervan Triyanto; Heri Sismoro; Arif Dwi Laksito (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2019)
Sufficient and equitable food availability is one of the pillars of the realization of food security. Every year rice production in Bantul Regency is always changing. Multiple Linear Regression Method is a forecasting method that uses more than two factors that can influence the results so that it can find maximum results. With this method of Multiple Linear Regression, get the mean absolute deviation (MAD) 0.101 with training data from 2009 - 2017. Multiple linear regression equations obtained were Y = 8307,561443282 + 5,9294543706657x1 + 118,28063200866x2 + 175,71009241484x3.